PENGARUH BRAND IMAGE DAN PERCEIVED QUALITY TERHADAP NIAT MENDAFTAR ULANG (REPURCHASE INTENTION) SISWA SMA AL MA’SOEM KE AMIK AL MA’SOEM - Ayi Mi’razul Mu’minin (Masoem University, 2017)
This study meant to analyze the influence of brand image and perceived quality on repurchase intention of senior high school students at Al Ma’soem Jatinangor to AMIK Al Ma'soem Jatinangor. The results of this study indicate; the brand image has a significant influence on the repurchase intention of SMA Al Ma’soem students to AMIK Al Ma'soem Jatinangor. While for the perception of quality there are some influences but rather weak and not significant enough to further influence the repurchase intention SMA Al Ma’soem students to AMIK Al Ma'soem Jatinangor. The F test results explained that the brand image and the perceived quality simultaneously affect the repurchase intention of Al Ma’soem senior high school student. The obtained R-square value amounted to 0.271 or 27.1%, it means that the simultaneous brand image and perceived quality contribute to the repurchase intention of Al Ma’soem senior high school students to AMIK Al Ma'soem Jatinangor which amounted of 27.1%.